Electrical Characterizations of Planar Ga2O3 Schottky Barrier Diodes - Shiyu Zhang; Zeng Liu; Yuanyuan Liu; Yusong Zhi; Peigang Li; Zhenping Wu; Weihua Tang (Micromachines, 2021)
In this work, a Schottky barrier diode (SBD) is fabricated and demonstrated based on the edge-defined film-fed grown (EFG) Ga2O3 crystal substrate. At the current stage, for high resistance un-doped Ga2O3 films and/or bulk substrates, the carrier concentration (and other electrical parameters) is difficult to be obtained by using the conventional Hall measurement. Therefore, we extracted the electrical parameters such as on-state resistance (Ron), Schottky barrier height (<semantics>ϕB</semantics>), the ideal factor (n), series resistance (Rs) and the carrier concentration (Nd) by analyzing the current density–voltage (J–V) and capacitance–voltage (C–V) curves of the Ga2O3-based SBD, systematically. The detailed measurements and theoretical analysis are displayed in this paper.